Roles of Chromolaena odorata, macrofauna, and forest edge on the decomposition rate of tree leaf litter in two types of seasonally dry tropical forest - Kasidit Rison; Marut Fuangarworn; Chatchawan Chaisuekul (Journal of Ecology and Environment, 2024)
Background: The forest edge of seasonally dry tropical forests (SDTF) is commonly invaded by Chromolaena odorata, which could affect the leaf-litter decomposition (LLD) rate through the litter fauna and the litter chemistry. We tested the effects of positions (edge vs. interior), C. odorata inclusion, and macrofauna inclusion using litterbags containing the two most dominant tree species from each forest type of SDTF (a dipterocarp deciduous forest and a mixed deciduous forest [MDF]), in northern Thailand. Results: The results showed that leaf litter decayed at the same rate between the forest edge and interior. A difference in the decomposition rate between the edge and interior was only found in the MDF and only when the composition of the litter contained a high nitrogen (C. odorata) and phosphorous content (Pterocarpus macrocarpus - a native tree of MDF). Exclusion of macrofauna resulted in slower decomposition rates, but this effect was not significant when combined with the edge condition. Conclusions: Our findings indicated that the forest edge condition has no directly significant effect on the LLD rate but is mediated through changes in the litter chemistry by inclusion of C. odorata litter.